2008
DOI: 10.1136/ard.2007.076679
|View full text |Cite
|
Sign up to set email alerts
|

Duration of preclinical rheumatoid arthritis-related autoantibody positivity increases in subjects with older age at time of disease diagnosis

Abstract: Corresponding author: V. Michael Holers, MD, Division of Rheumatology, University of Colorado at Denver and Health Sciences Center, Barbara Davis Center, 1775 North Ursula Street, Aurora, Colorado 80045, Phone: (303) Fax: (303) 724-7581, Michael.Holers@uchsc.edu. Address for reprint requests: Same as above * These two authors contributed equally to the study. COMPETING INTERESTSThe authors declare that they have no competing interests. AUTHORS' CONTRIBUTIONSDM participated in the design and analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(147 citation statements)
references
References 26 publications
10
128
1
3
Order By: Relevance
“…However, our case did not exhibit any symptoms or signs of RA in the presence of high titers of anti-CCP antibodies. Antibodies to citrullinated pep- tides have been demonstrated to precede the development of RA by several years (12), as observed in the present case. It is suggested that in addition to the synthesis of anti-CCP antibodies, additional events are needed to trigger the clinical onset of RA.…”
Section: Discussionsupporting
confidence: 81%
“…However, our case did not exhibit any symptoms or signs of RA in the presence of high titers of anti-CCP antibodies. Antibodies to citrullinated pep- tides have been demonstrated to precede the development of RA by several years (12), as observed in the present case. It is suggested that in addition to the synthesis of anti-CCP antibodies, additional events are needed to trigger the clinical onset of RA.…”
Section: Discussionsupporting
confidence: 81%
“…The risk of unrecognized disease speaks to the importance of rheumatologic evaluation in patients presenting with NMO/NMOSD in order to adequately rule out coexistent CTD. Similarly, in the 2 patients with NMO alone, the presence of antinuclear and SSA antibodies could represent preclinical autoimmunity prior to the onset of symptomatic disease, as described in other autoimmune conditions such as rheumatoid arthritis (45,46). Continued monitoring of these patients is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 273 first-degree relatives, 59 (22%) were recruited from 29 families in whom the RA proband was not included in the study for a variety of reasons, including lack of availability, death, etc. The median number of firstdegree relatives per family was 3 (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The distribution of first-degree relatives relative to family size is available online at www.proteome.ca.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we have shown that approximately one-third of the first-degree relatives of North American Native patients with RA are seropositive for anti-citrullinated protein antibodies (ACPAs) and/or rheumatoid factor (RF) (9). Since it has been shown in several other populations that these two RA-associated autoantibodies are often present in the serum of individuals months to years prior to the onset of clinically detectable RA (10)(11)(12), first-degree relatives from this population appear to be at risk of future development of the disease.…”
mentioning
confidence: 99%